Pain and motor complications in Parkinson's disease. Issue 7 (20th March 2006) - Tinazzi, M; Del Vesco, C; Fincati, E; Ottaviani, S; Smania, N; Moretto, G; Fiaschi, A; Martino, D; Defazio, G
Abstract : Aims: To study the association of pain with motor complications in 117 patients with Parkinson's disease. Methods: Patients were asked to refer any pain they experienced at the time of study and lasting since at least 2 months. Basic parkinsonian signs and motor complications (including motor fluctuations and dyskinesia) were assessed and Unified Parkinson's Disease Rating Scale (UPDRS) motor score part III (during on) and part IV were calculated. Information on age, sex, duration of disease, use of dopamine agonists and levodopa, years of levodopa treatment and current levodopa dosage, medical conditions possibly associated with pain, and depression were collected. Single and multiple explanatory variable logistic regression models were used to check the association of pain with the investigated variables. Results: Pain was described by 47 patients (40%) and could be classified into dystonic (n.19) and non dystonic pain (n.16); in 12 patients both types coexisted. Multiple explanatory variable logistic regression models indicated a significant association of pain with motor complications (adjusted OR, 5.7; 95% CI, 2 to 16.5; p = 0.001). No association was found between pain, dystonic or non dystonic, and the other investigated variables including medical conditions known to be associated to pain in the general population. There was a significant correlation (r = 0.31, p<0.05) between severity of pain (measured on a Visual Analogue Scale) and severity of motor complications (UPDRS part IV). Conclusions: Pain may be a representative feature of Parkinson's disease frequently associated with motor complications. The association is independent of a number of potentially relevant demographic and clinical variables.